Peran Guru Pendidikan Agama Islam Dalam Meningkatkan Etika Siswa di SMKN 1 Tembilahan Hulu - Zulkifli (Universitas Majalengka, 2024)
Ethics are a set of rules and principles of human life. The good and bad of a person is seen from the ethics or character that he has. Therefore, the process of forming ethics or character must be carried out by educating, guiding and getting used to it continuously so that students have good ethics. The purpose of this study was to determine the role of Islamic religious education teachers in improving student ethics. The research used is Quantitative research, data collection techniques used in this study are observation and documentation. The results of the analysis of the study through observation are 85% which is categorized as